Primary Intraosseous Carcinoma, Not Otherwise Specified with Ameloblastic Carcinoma Features in a Middle-aged Woman - Stephen Utama Candinegara; Dewa Gede Subawa; Renaningtyas Tambun (Cermin Dunia Kedokteran, 2022)
Primary Intraosseous Carcinoma, Not Otherwise Specified (PIOC, NOS) is an extremely rare neoplasm defined as squamous cell carcinoma in the mandible, presumably from the residue of odontogenic epithelium. The diagnosis is often challenging, and the prognosis is poor. The treatment of choice is surgical excision but usually declined for cosmetic reasons. A 41-year-old Melanesian woman with a mass in her right jaw since two years ago but rapidly growing in the last six months, accompanied with pain. Irregular hard mass was found in the right mandible. Radiology studies revealed lytic tumors, likely infiltrating. No metastasis was found. The first biopsy revealed acanthomatous ameloblastoma, and the second biopsy revealed pseudoepitheliomatous hyperplasia. Wide excision was then conducted with pathology results of PIOC and NOS with some features of ameloblastic carcinoma. This case may arise from a previous benign precursor. Further genetic information may be needed. The treatment of choice is surgical excision. The prognosis needs further follow-up.   Primary intraosseous carcinoma, not otherwise specified (PIOC, NOS) merupakan keganasan odontogenik yang langka. Diagnosisnya sulit dengan prognosis buruk. Tata laksana utama adalah bedah eksisi yang cenderung ditolak karena alasan estetik. Seorang perempuan ras Melanesia usia 41 tahun, mengeluh benjolan rahang kanan sejak dua tahun dan makin membesar terutama 6 bulan terakhir disertai nyeri. Massa tidak teratur dengan batas tidak jelas di mandibula kanan dengan ukuran 10 x 8 x 4 cm. Pemeriksaan radiologis menegaskan massa infiltratif, tetapi tidak menemukan anak sebar. Biopsi awal menunjukkan ameloblastoma, biopsi selanjutnya menunjukkan pseudoepitheliomatous hyperplasia. Eksisi luas dilakukan dan patologi menemukan PIOC, NOS dengan sebagian ciri ameloblastic carcinoma. Patologi dari tiga biopsi menunjukkan massa jinak odontogenik yang mengalami inflamasi kronis kemudian menjadi ganas. Prognosis masih belum bisa dipastikan.